PENGARUH TAHAPAN DAUR HIDUP PERUSAHAAN, GOOD CORPORATE GOVERNANCE,SET KESEMPATAN INVESTASI' ALIRAN KAS BEBAS DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN: TINJAUAN TEORITIS - Werner R. Murhadi (Center for Economic Studies Universitas Katolik Parahyangan, 2008)
This article aims to study Firm Life cycle, Good corporate Governance, Investment opportunity set, Free Cash Flow and Ownership Structure that can influence value of the firm. The Firm in growth industry tends to increase in value of the firm, vice versa. Literature review exposed that good corporate governance can minimize agency conflict between manager and shareholder, and then it can be positive relationship with value of the firm. The Firms that have many investment opportunities can have positive impact to value of the firm. Free cash flow has both positive and negative relationship to the value of the firm. If Firm uses free cash flow to invest in a good project, value of the firm will be increased. The last, ownership structure based on convergence argument can increase value of the firm. Based on entrenchment argument, ownership structure can make majority shareholder use firm's resource to their importance.